(untitled) (Biological Sciences - PJSIR, 2007)
. Effect of i ndole-3-aceti c acid and n aphthal ene acet ic acid treatments on the establ ish ment of damask rose ( Rosa damascena M i l l.) cutti ngs i n d i fferent growth med i a was eva l u ated an d it was revea led that the average n u mber of roots and root i ng percentage grad uall y i ncreased with i ncrease i n hormone concentrati on. The maxi m u m n u m ber of roots ( 1 5.72), rooti ng percentage (94.1 7 %), p l ant height ( 1 34.2 cm), p l ant spread (46.3 cm), pri mary shoots (6.3), secondary shoots (25) and survival percentage (94.72%) was recorded for 50 mg/I naphthalene acetic acid appl ication; the results were superior to i ndol e-3-acetic acid, t h e optim um l evel bei n g i n the range of 50 and 75 mg/I. o such concl usion could be d rawn for i ndol e-3-acetic acid. The leaf mold was the best growth medi um gi vi ng the max im um n umber of roots per cu tti ng (10.78), rooti ng percenta ge (87.68%), pl ant h eight ( 1 25 . 1 cm), pl ant spread (37 cm), pri mary shoots (5.2), secondary shoots ( 1 9.48) and surv i va l percent age (85.67%), fol lowed by soi l + leaf mold , whi le soi l med i um was the l east effective .